BYĆ ROZTROPNYM, CZYLI PRZEWIDYWAĆ Z MYŚLI FILOZOFICZNEJ SENEKI MŁODSZEGO O CNOCIE „PRUDENTIA” - Budzanowska, Dominika (Colloquia Litteraria, 2009)
Wisdom is foresight. Philosophical thought of Seneca the Younger about the virtue of prudentia One of the most important themes in the literary legacy of Seneca, a Roman stoic philosopher and tutor of young Nero, is the science on virtues. Withing its aretology there is the virtue of prudence, prudentia, whose definition is: facienda providere. By way of example, we may understand it as predicting the effects of, for instance, enacting a specific law. The virtue of prudentia refers also to proper counseling, actually in different situations: prudentia suaserit; it recommends to make good use of present times, to care for the future, think and deliberate. To live prudently means to live for the moment, to take advantage of our life time of in a good way.